2010
DOI: 10.1007/s00415-010-5742-x
|View full text |Cite
|
Sign up to set email alerts
|

Is central fatigue in multiple sclerosis a disorder of movement preparation?

Abstract: We tested the hypothesis that fatigue in MS is related to a dysfunction in cortical areas involved in movement preparation. Thirty-three patients with clinically definite MS (16 with fatigue MS-F, 17 without fatigue MS-NF) and a relapsing-remitting course, matched for disease severity and duration, disability scores and level of depression were enrolled. They underwent a combined assessment with magnetic resonance imaging (MRI) and transcranial magnetic stimulation (TMS) and, for the electrophysiological study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
91
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 40 publications
3
91
1
Order By: Relevance
“…Additionally, the short-interval intracortical inhibition (SICI), which reflects the GABAergic intracortical inhibitory mechanisms, was examined in two trials that yielded inconsistent outcomes. In other words, while Liepert et al found reduced SICI in highly fatigued MS patients compared to those with low fatigue [116], Morgante et al failed to obtain similar results [135]. The observed discrepancy might be due to differences in inclusion criteria with relatively more disabled patients in the first work.…”
Section: Physiological and Neurochemical Correlates Of Ms Fatiguementioning
confidence: 89%
See 1 more Smart Citation
“…Additionally, the short-interval intracortical inhibition (SICI), which reflects the GABAergic intracortical inhibitory mechanisms, was examined in two trials that yielded inconsistent outcomes. In other words, while Liepert et al found reduced SICI in highly fatigued MS patients compared to those with low fatigue [116], Morgante et al failed to obtain similar results [135]. The observed discrepancy might be due to differences in inclusion criteria with relatively more disabled patients in the first work.…”
Section: Physiological and Neurochemical Correlates Of Ms Fatiguementioning
confidence: 89%
“…TMS permits study of various interhemispheric and intrahemispheric processes. Three studies examined corticospinal excitability in fatigued and non-fatigued MS patients, but could not detect any relationship between fatigue and any of the following: motor threshold, motor evoked potentials (MEP) amplitude or central motor conduction time (CMCT) [116,135]. To note, motor threshold depends on the biophysical properties of motor neuron membranes; MEP amplitude and CMTC mainly assess the excitability and integrity of the corticospinal pathways [28].…”
Section: Physiological and Neurochemical Correlates Of Ms Fatiguementioning
confidence: 99%
“…The observed increases in positive work may also contribute to the 13 reported increase in effort and fatigue in people with MS, compared to healthy controls. People with MS are likely to increase the underlying central corticomotor activity needed to increase or maintain muscle power during walking, which could contribute further to walking-induced fatigue [38,[53][54][55].…”
Section: Kineticsmentioning
confidence: 99%
“…To investigate this hypothesis, they recruited 33 patients with RRMS, who underwent MRI and transcranial magnetic stimulation (TMS). Results showed a significant increase in the burden of lesion load in frontal areas correlating with the degree of fatigue, expressed by the fatigue severity scale (FSS) score, thus demonstrating that frontal lobe impairment is associated with fatigue in MS [3].…”
Section: Clinical Aspectsmentioning
confidence: 97%
“…Patients with fatigue (representing 40 % of the cohort) had higher expanded disability status scale (EDSS) scores, as well as a more pronounced CC atrophy [2]. Morgante et al [3] tested the hypothesis that central fatigue in MS might be correlated with a dysfunction in the cortical areas upstream of the pyramidal tract involved in motor planning and preparation. To investigate this hypothesis, they recruited 33 patients with RRMS, who underwent MRI and transcranial magnetic stimulation (TMS).…”
Section: Clinical Aspectsmentioning
confidence: 98%